Serious games na educação em saúde para prevenção de infecções sexualmente transmissíveis em adolescentes: uma revisão sistemática - Zanarotti, Elaine [UNIFESP] (2018)
Background: Increasing rates of Sexually Transmitted Infections (STI) and Acquired Immunodeficiency Syndrome (AIDS) in adolescents require the adoption of effective preventive measures and actions in sexual health education. In this respect, among the possible educational strategies to be used, we highlight the potential of digital educational games, known as serious games. However, it is necessary to deepen the studies on the collection of evidence of this resource effectiveness in adolescent sexual health education. Objectives: To identify the effectiveness of serious games in the prevention of STI in adolescents, in relation to knowledge about STI and HIV / AIDS and safe sex, self-efficacy in condom use and self-efficacy in changing sexual risk behaviors. Method: Systematic review according to the recommendations presented by the Cochrane Collaboration Interventions Systematic Review Guide with a textual search until February 28, 2018, in the following databases: MEDLINE (since 1966), Embase (since 1980), CENTRAL (since 1982), BVS (since 1998) and SciELO (since 1997). Selection of studies: We included studies on serious games interventions aimed at preventing STI in individuals between 12 and 18 years of age, according to the inclusion and exclusion criteria defined in this review. Data collection: A comprehensive bibliographic survey was conducted to identify randomized controlled clinical studies, published and unpublished, until February 28, 2018, in Portuguese, English and Spanish, with the following descriptors: video games, adolescents, sexually transmitted diseases, health education Results: The study search process resulted in the retrieval of 831 references, of which 50 potentially relevant articles were selected for complete reading. Of these, seven randomized controlled clinical trials were selected and included a sample of 1.877 participants with an average age between 12 and 17 years. The evaluated outcomes showed significant positive effects on STI and HIV / AIDS knowledge and safe sex, and improvements in self-efficacy in relation to behavior change aimed at reducing risks. Only one study reported increased self-efficacy on condom use and increased frequency of use in sexual acts. The good acceptance and usability of the interventions and the lack of adverse effects with respect to the applied interventions were observed. None of the studies had a low risk of bias for all items of methodological quality assessment. The lack of methodological detail in most studies has led to uncertainties about possible biases, as well as difficulty in determining the completeness of the results and conclusions presented. Conclusion: It was not possible to determine the effectiveness of serious games in the prevention of STI in adolescents in relation to the researched outcomes, due to the quality of the evidence. But, there are indications of positive effects, mainly on the increase of knowledge about STI and HIV / AIDS. However, more randomized controlled trials with more homogeneous methodologies and studies that verify their results and effectiveness in the long term are needed.